Investigating the activity of indigenous microbial communities from Italian depleted gas reservoirs and their possible impact on underground hydrogen storage - Bellini, Ruggero; Vasile, Nicolò Santi; Bassani, Ilaria; Vizzarro, Arianna; Coti, Christian; Barbieri, Donatella; Scapolo, Matteo; Pirri, Candido Fabrizio; Verga, Francesca; Menin, Barbara (Frontiers in Microbiology, 2024)
Renewable energies will play a central role in both greenhouse gas reduction and decarbonisation by 2050. In Italy, the use of H2 produced from renewable energies and the consumption of natural gas are expected to grow considerably Currently, underground storage of natural gas in depleted reservoirs, aquifers and salt caverns is well-established thanks to the skills and experience gained in a century on nearly 700 facilities worldwide. However, new challenges arise when it comes to storing hydrogen, the main one likely being related to the occurrence and activity of indigenous microbial populations in deep geological formations. Microorganisms are known to act as reducing agents for the main geo-microbiological reactions, especially acetogenesis, methanogenesis and sulphate reduction, thus they could significantly alter the composition of the stored gas. In a previous study, four Italian natural gas reservoirs were characterized both from a chemical and microbiological point of view, and predictive functional analyses were carried out with the perspective of underground hydrogen storage (UHS). In the present study, we monitor the activation of hydrogenotrophic methanogens, sulphate reducing and acetogenic bacteria in preserved formation waters sampled from the same four reservoirs during optimized batch cultivation assays in response to different gas blends containing H2. Thus, we could assess the effects of the microorganism metabolisms on possible future storage operations and more at large the storage safety.